BIOCHEMICAL AND MORPHOLOGICAL CHARACTERIZATION OF PSEUDOMONAS FLUORESCENS ISOLATES AND ITS EFFICACY AGAINST DAMPING-OFF IN CHILLI (Journal of Plant Disease Sciences, 2025)
This study examines three isolates of Pseudomonas fluorescens (PDKV Pf1, Pf2, Pf3) obtained from the chilli rhizosphere, focusing on their biochemical and morphological characteristics and their efficacy in suppressing Pythium aphanidermatum, the causal agent of damping-off in chilli. The isolates were evaluated for their ability to produce hydrogen cyanide (HCN) and indole-3-acetic acid (IAA), essential plant growth-promoting compounds. Morphologically, all isolates were identified as gram-negative and rod-shaped. Among them, PDKV Pf1 displayed the strongest biochemical activity, testing positive for catalase, oxidase, triple sugar iron (TSI), arginine dehydrolase, starch hydrolysis, H₂S production, methyl red test, citrate utilization, HCN production, and gelatin liquefaction.
Keywords: Chilli; Pseudomonas; Pseudomonas fluorescens; Pythium aphanidermatum; Biochemical